Analisis Realisasi Ketahanan Pangan Desa Patempuran melalui BUMDes: Optimalisasi Kedelai, Peternakan sebagai Pilar Ekonomi Mandiri - Deviana Putri Alamanda; Nurizzatil Ramadhani; Emilianti Dewi Ponidi; Marva Dosi Januarta; Ziyad Hibatullah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study investigates the implementation of the food security program and the establishment of independent economic pillars in Patempuran Village, Kalisat, Jember, by focusing on the central role of the Patempuran Sejahtera Village-Owned Enterprise (BUMDes). Using a qualitative approach with a case study design, this study explores the strategies, achievements, and challenges of program implementation in integrating two of the village's main agricultural potentials: soybean cultivation and livestock. The core finding is the formation of an Integrative Management Model in which the BUMDes acts as the primary institutional driver, synergizing the soybean and livestock sectors. The BUMDes successfully fulfills its dual function: as an economic institution (generating a net profit of approximately IDR 9 million from 1.8 hectares of soybean cultivation) and as a social institution empowering the community through job creation and additional income. This success is closely linked to the high level of active community participation, in line with Stakeholder Theory in strengthening legitimacy and a sense of shared ownership. However, implementation faces significant challenges, including irrigation constraints in hilly areas, livestock health risks, and a manual financial recording system (based on a simple Excel spreadsheet), which limits managerial capacity and full accountability. This study recommends immediate modernization of the accounting system, strategic investment in irrigation infrastructure, and strengthening intensive technical assistance to ensure long-term sustainability and equitable partner productivity.